Application of video tutorials as a media for learning front punch of pencak silat to improve students' motivation and skills learning outcomes - Alhuda, Muhammad Yohan; Dafun JR, Procopio B.; Yulfadinata, Afifan (Bima Loka: Journal of Physical Education, 2024)
To determine effective learning outcomes in learning activities, motivation and learning outcomes are 2 very important components. The utilization of video instructional exercise learning media is one component of the apparatus to form fruitful instructing and learning exercises. Knowing the impact and how much impact it has on its usage. The aim of this investigation is to supply video instructional exercise learning materials to progress fundamental Pencak Silat front assault development abilities. This inquire about applies a one-group pretest and posttest design. Utilizing information appraisal models, abilities appraisal, and learning inspiration surveys. The tests utilized in this inquire about were 32 tests, and this number was decided based on the number of understudies within the course. The results of the study showed that the media used can affect motivation (t = 2.509, p = 0.018), knowledge (Z= 5.660, p = 0.000), and skills (Sitting cross-legged Z= 4.967, p = 0.000; Stand up straight Z= 5.035, p=0.000; Sawhorse Z= 4.998, p= 0.000; and move Z= 5.009, p= 0.000). We recommend that teachers can develop teaching materials by utilizing technology so that learning is more motivating and makes it easier for students to learn teaching materials.